Character Education as a Strategy to Prevent Promiscuity Among Senior High School Students in Merauke - Kristiani Butar-Butar; Agus Basuki; Marwan Marwan; Agus Herwanto; Agung Prihatmojo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Character education plays a critical role in shaping students’ values and behaviors, serving as a preventive measure against social issues such as promiscuity. In Merauke, a region with distinct cultural and social dynamics, addressing adolescent behavior through character development is essential. This qualitative study employed a case study design to explore the impact of character education on preventing promiscuity among high school students in Merauke. Conducted in 2023, the research involved students, parents, and teachers at a local high school. Data were gathered through in-depth interviews and direct observations, then analyzed thematically to examine the roles of educators and families in guiding students’ moral development. Findings indicate that effective character education—integrating moral values, ethics, and social responsibility—significantly contributes to reducing risky behaviors among students. Collaboration between schools, parents, and communities enhances the effectiveness of these programs. Participants reported noticeable improvements in students’ sense of responsibility and decision-making. However, challenges such as limited parental awareness and the pervasive influence of technology hinder optimal outcomes. The study highlights the importance of tailoring character education to the unique cultural context of Merauke. To address ongoing challenges, greater efforts are needed to involve families and integrate local values into the curriculum. Strengthening character education holistically may offer a sustainable strategy for mitigating adolescent promiscuity in the region.